Persistent Gender and Racial Hierarchies: Marriage Migration and Mixedness in Morocco from the French Protectorate to the Present - Catherine Therrien; Catherine Phipps (L’Année du Maghreb, 2023)
This article presents a historical and anthropological approach to mixed marriages in Morocco, tracking the continuities and changes between the French colonial period and contemporary experiences to see how attitudes towards mixed couples changed in Morocco throughout the French protectorate, in the post-independence period and the increasingly globalised world of the 21st century. This interdisciplinary approach combines historic data (primarily from a 1949 study into mixed marriages conducted by the colonial government as well as magazines, novels and memoirs) with 52 anthropological semi-structured interviews (conducted in Morocco between 2018 and 2022) with children of mixed couples and some of their parents.We examine first how the demographic make-up of mixed couples and where they choose to settle has shifted, looking at their gender split, their countries of origin, their occupations and where they met. This has diversified considerably throughout the 20th century: the individuals come from a much larger number of countries (no longer primarily Moroccan soldiers who returned from France with French women) and Moroccan women are now more likely to travel abroad. But gender still impacts mobility as the country of settlement is still often linked to the husband’s job. We then compare how in some cases legal and religious restraints have affected which mixed couples can marry. Although European men could marry Moroccan women, the French colonial authorities sought to ban European wives or partners of Moroccan men from entering Morocco because they believed these relationships would threaten the hierarchies of colonial rules. However, in contemporary Morocco migration is considerably easier for individuals from the Global North. Today the Moroccan family law (Mudawana) states that a foreign man has to convert to Islam if he wishes to marry a Moroccan Muslim woman. What is forbidden has changed, but women’s freedom remains subject to external pressures to maintain social cohesion. Finally, we examine the emotional motivations behind choosing mixed marriages, often overlooked by studies of migration, arguing that mixed marriage in Morocco has always shown a “desire for elsewhereness” and offered a space of freedom, a way to embrace new possibilities and turn away from certain social norms. In the 20th century, in the colonial and post-independence period, many Moroccan men used mixed marriage as a way to escape traditional pressures to pay a bride price (sdaq) to a Moroccan woman’s family. Some Moroccan men also expressed colonialist ideas that European women were more “evolved” and would make better partners than Moroccan women as they were more educated because of gender inequalities in access to education. This has changed due to Moroccan women’s improved access to education. But emotions are still at the heart of these experiences of intimacy across racial, national and religious borders. Contemporary and historical couples see mixedness as imbued with new opportunities to express their desire for change, for a new way of living and for creativity. Mixed marriages provide a change to re-evaluate customs and lifestyles, but these are also deeply intimate relationships born out of emotional attachment. This article reminds readers that marriage migration is, at heart, a migration for love. This love, and the feeling of possibility it offers, can be considered a threat to existing power structures. We argue that in post-independence Morocco, mixed marriages are no longer considered a threat to political power but that they still reveal the existence of persistent racial and gender symbolic boundaries. Indeed, social perception of mixed couples has shifted from a fear of neo-imperialism to a feeling of opportunities in a globalized world, but gender and racial hierarchies still prevail as significant symbolic boundaries that shape mixed couples and attitudes towards them.